Chasing Storms: Temporal Work to Foster Group Engagement under Uncertainty - Kent, Derin; Granqvist, Nina (Academy of Management Journal, 2025)
Experiences of group engagement have a significant impact on members’ performance and satisfaction with work. In temporally uncertain settings, however, unpredictable transitions between idle and busy periods disrupt engagement. Through an ethnographic study of storm chasing teams in Tornado Alley, we investigate how groups foster engagement under uncertainty. We found that while efficient coordination helped teams get to storms, it could frustrate members’ engagement with tasks across unpredictable transitions. We develop a process model explaining how groups use temporal work to foster immersive episodes of engagement across transitions that are hard to control or predict. We show that broadening focus and compressing duration foster experiences of temporal control that enable engaging transitions into busy periods of work, whereas narrowing focus and extending duration foster experiences of immersive duration that enable satisfying transitions into idle periods. We develop a temporal perspective to engagement at work, showing how groups set the temporal context within which they encounter work episodes and how this context enables or constrains engagement. We also advance a durational perspective for organizational temporality research, elucidating how experiences of duration represent a key issue to be managed in organizations.